Evaluating the Use of Warfarin Using the HAS-BLED Score and INR on Atrial Fibrillation Patients at Harapan Kita National Heart Center - Meva Sari Chandra; Shirly Kumala; Sesilia Andriani Keban (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2020)
Patients with atrial fibrillation are associated with a 4-5-fold risk of having a stroke. The most effective treatment for atrial fibrillation is to prevent the formation of blood clots by administering anticoagulant drugs. Warfarin is an anticoagulant drug that has a narrow therapeutic index with side effects of the risk of bleeding; hence it needs supervision in its use. In this study, the HAS-BLED score was used to measure major bleeding risk and as a value representing each risk factor for bleeding. The bleeding risk can be prevented by maintaining a warfarin response in the therapeutic range with an INR (International Normalized Ratio) measurement 2-3. This study was an observational study conducted with retrospective data collection through medical records of patients with a primary diagnosis of atrial fibrillation who received oral warfarin anticoagulant therapy at Harapan Kita National Heart Center in the period of January-December 2017. Using a sample of 40 patients who met the inclusion criteria. According to the data, found that atrial fibrillation patients who received oral warfarin therapy 55% were male patients, while 45% were female patients. Patients with atrial fibrillation who got the most oral warfarin therapy were patients who were over 40 years old with 90% of the total sample, with the highest group in patients aged 50-54 years with 22.5%. The HAS-BLED values arranged from 0-9, the percentage of patients who had HAS-BLED values of 0, 1, 2 respectively at 7.5%, 42.5%, 30%. The HAS-BLED score ≥ 3 showed patients classified as at high risk of bleeding by 20%. The most risk factors based on HAS-BLED score from all study samples were 18 patients with abnormal kidney or 45%. The average INR score in patients at high risk of bleeding showed that 37.5% had an average INR score in the target ratio score of INR 2-3.